PEMANFAATAN SOSIAL MEDIA SEBAGAI SARANA PEMBELAJARAN DI ERA DIGITAL - Anita Candra Dewi (JURNAL SKRIPTA, 2024)
The purpose of this study was to determine the impact of the use of social media as a medium for language learning for students. Field facts where the use of social media in Indonesia shows that Indonesia is the country with the most social media users. Not a few schools and universities in Indonesia utilize technological advances as one of the media in learning, one of which is language education. The research method used is a qualitative method, using literature studies, namely examining the impact of the use of social media in learning Indonesian, both regarding positive and negative effects. This is also motivated by the use of social media which has recently been widely misused by students. The results of the study show that the use of social media in learning Indonesian for students has a variety of complex impacts. On the one hand, social media offers various benefits, such as high accessibility to learning materials, ease of interacting with peers and teachers, and increasing learning motivation. In addition, social media can also enrich students' learning experiences through a variety of creative and interactive content. However, on the other hand, uncontrolled use of social media can have negative impacts, such as distraction, invalid information, and the formation of poor language habits. The conclusion of the study is that the use of social media in learning Indonesian has great potential to increase the effectiveness of learning. However, its success depends greatly on how social media is utilized.